Response to letter to the editor regarding free flap reconstruction of posterior trunk soft tissue defects: single institution experience and systematic literature review - AKDENİZ DOĞAN, ZEYNEP DENİZ (My University, 2022)
We thank the authors for their valuable contribution to our article, “Free Flap Reconstruction of Posterior Trunk Soft-Tissue Defects: Single-Institution Experience and Systematic Literature Review.”1 In their letter, Leach et al. describe their previously published technique in which an arteriovenous loop is created from femoral artery to femoral vein with a single end-to-side anastomosis while maintaining the continuity between the great saphenous vein and femoral vein.2 They also present their recent case with a large lumbosacral defect successfully reconstructed with a latissimus dorsi muscle flap utilizing their arteriovenous technique. Provided the correct geometry and defect location, we strongly support and fully endorse their saphenous vein arteriovenous loop transposition procedure.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Plastik ve Rekonstriktif Cerrahi; Medicine; Health Sciences; Surgery Medicine Sciences; Plastic and Reconstructive Surgery; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery